2018
DOI: 10.1038/s41598-018-27737-y
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells in Combination with Hyaluronic Acid for Articular Cartilage Defects

Abstract: Mesenchymal stem cells (MSCs) and hyaluronic acid (HA) have been found in previous studies to have great potential for medical use. This study aimed to investigate the therapeutic effects of bone marrow mesenchymal stem cells (BMSCs) combined with HA on articular cartilage repair in canines. Twenty-four healthy canines (48 knee-joints), male or female with weight ranging from 5 to 6 kg, were operated on to induce cartilage defect model and divided into 3 groups randomly which received different treatments: BMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 47 publications
2
69
0
3
Order By: Relevance
“…Glycosaminoglycan is an alkaline glycol polymer that becomes heterochromatic when it is reacted with the alkaline dye toluidine blue [13]. In our study, blue-purple heterochromatic granules were observed in chondrocytes, and small amounts of heterochromatic granules were observed around the chondrocytes, indicating that glycosaminoglycan and other extracellular matrix components were secreted by the chondrocytes.…”
Section: Discussionsupporting
confidence: 51%
“…Glycosaminoglycan is an alkaline glycol polymer that becomes heterochromatic when it is reacted with the alkaline dye toluidine blue [13]. In our study, blue-purple heterochromatic granules were observed in chondrocytes, and small amounts of heterochromatic granules were observed around the chondrocytes, indicating that glycosaminoglycan and other extracellular matrix components were secreted by the chondrocytes.…”
Section: Discussionsupporting
confidence: 51%
“…This is mainly aimed to prevent health issues of the pets. UCB may not be suitable source to harvest MSCs due to limited available volume of blood and cell concentration therein (Lim et al, BM-MSC CD44, CD73, CD90, CD105 CD14, CD34, CD45 Neurogenic Ryu et al (2012) BM-MSC CD29, CD44, CD90, OCT3/4, SOX2, NANOG CD34, CD45, SSEA-3, SSEA-4, TRA-1-60, TRA-1-81 (Continues) replacements (Enciso et al, 2018;Li et al, 2018). After confluent growth of 70-80%, the cells are enzymatically detached to reseed to lower densities and passaged for continual growth and expansion (Gade et al, 2013;Gugjoo et al, 2015).…”
Section: Sources Of Dmscsmentioning
confidence: 99%
“…[12] Although there are various types of biocompatible and injectable stem cell scaffolds such as poly(lactic acid) derivate, [13] hyaluronic acid, [14] and supramolecular hydrogel, [15] the controlled differentiation of stem cells is of foremost importance to the attainment of the desired tissue construction. [12] Although there are various types of biocompatible and injectable stem cell scaffolds such as poly(lactic acid) derivate, [13] hyaluronic acid, [14] and supramolecular hydrogel, [15] the controlled differentiation of stem cells is of foremost importance to the attainment of the desired tissue construction.…”
Section: Introductionmentioning
confidence: 99%